An R2R3-MYB Transcription Factor Positively Regulates the Glandular Secretory Trichome Initiation in Artemisia annua L. - Qin, Wei; Xie, Lihui; Li, Yongpeng; Liu, Hang; Fu, Xueqing; Chen, Tiantian; Hassani, Danial; Li, Ling; Sun, Xiaofen; Tang, Kexuan (Frontiers in Plant Science, 2021)
Artemisia annua L. is known for its specific product “artemisinin” which is an active ingredient for curing malaria. Artemisinin is secreted and accumulated in the glandular secretory trichomes (GSTs) on A. annua leaves. Earlier studies have shown that increasing the GSTs density is effective to increase artemisinin content. However, the mechanism of GSTs initiation is not fully understood. To this end, we isolated and characterized an R2R3-MYB gene, AaMYB17, which expressed specifically in GSTs of shoot tips. Overexpression of AaMYB17 in A. annua increased the GSTs density and enhanced the artemisinin content. Whereas, RNA interference of AaMYB17 resulted in the reduction of GSTs density and artemisinin content. Additionally, neither overexpression lines nor RNAi lines showed abnormal phenotype in plant growth and the morphology of GSTs. Our study demonstrates that AaMYB17 is a positive regulator of GSTs initiation, without influencing the trichome morphology.